MALAYSIA RESILIENT INITIATIVES: CASE STUDY OF MELAKA INTO RESILIENT CITY - Jamaliidin, Intan Syafinar; Sulaiman, Noralfishah (PLANNING MALAYSIA, 2018)
Asia experienced 70% of all the disasters in the world and there is no indication that this will decline in the future. The disaster experienced by a city is mostly caused by the combination and collision of climate change, urbanization, social-economic instability, terrorism, natural disaster, cyber-attack, poverty, and endemic outbreak. The crisis fallen upon a city has captured attention of many audiences, thus in order to conquer the issues, city needs to be resilient in order to face and overcome the situation. Melaka was declared as a world heritage site and the government are taking serious efforts in order to maintain its heritage site by making it a resilient city. This article discusses the policy related initiatives taken by Melaka in preparing the city into resilient state. This is done by using literature and document analysis method on relevant reports, policies and literatures. The output of the research would be beneficial to the state of Melaka in the context of local authorities preparing strategic directions and managing urban development in order to become a resilient city.